Auge y ocaso de la primera sociedad minera de América. Santo Domingo 1503-1520 - Francesco D’Esposito; Auke P. Jacobs (Nuevo mundo - Mundos Nuevos, 2015)
In 1502 following upon the arrival of Nicolás de Ovando’s expedition of colonization, the period of Columbian experiments is over and the construction of the first colonial society of the New World begins. The aim of the settlers is the search for gold. The arrival of the immigrants is massive till 1510, when the gold-bearing production of the island reaches its summit. The mining industry totally weights down the Taino’ support and they die out rapidly. Together with the fall of the native labour and collapse of the deposits of gold also the production of the metal reduces. In the second decade of the century is overcome by that of Puerto Rico and Cuba. By the twenties the production becomes irrelevant and the society of the isle based on mining becomes a society based on agriculture and cattle breeding. At the same time the most part of the Spanish who have not taken advantage from the mining industry and for whom gold hasn’t brought the hoped enrichment starts again the emigration route to conquer other parts of the New World.